About questioning people harmed by offences under art. 197–199 of the Polish Penal Code. Study on application of law - Sławomir Tkacz (Acta Universitatis Lodziensis Folia Iuridica, 2018)
The subject matter of the considerations is the issue of the application of art. 185c § 2 of the [Polish] penal procedure code, according to which people harmed by offences under art. 197–199 p.c. are interrogated as witnesses at a court session. This provision introduces a special mode of interrogation of a victim witness while conducting proceedings in cases involving sexual offences. The intention of the legislator is to guarantee the victims of these crimes a higher standard of protection. In the course of the conducted analyses, the findings made by the Commissioner for Citizens’ Rights in the course of the proceedings were presented, aiming at determining how the legislator’s objectives are implemented in practice. It has been noticed that often several dozen days pass between the notification of a crime and the questioning of the victim. As a result, the intention of the legislator cannot be implemented. The undertaken analyses were concluded with a theoretical reflection on the effectiveness of legal provisions. In conclusion, it was pointed out that effectiveness requires, in particular, taking into account the relationship between the behavior of recipients and the goals assumed by the legislator.